CHARACTERIZATION OF BIO EXTRACTS FROM ELUSINE INDICA, CASSYTHA FILIFORMIS AND MORUS RUBRA BY FTIR AND GC-MS FOR CORROSION INHIBITION OF METALS IN HCL AND H2SO4 SOLUTIONS - Nze, Soronnadi Michael; Ezeugo, J. O.; Umeuzuegbu, J. C. (FUDMA Journal of Sciences, 2025)
This study explores the corrosion inhibition efficacy of bio extracts from Elusine indica, Cassytha filiformis, and Morus rubra on mild steel, aluminum, and zinc in acidic environments (1 M HCl and 0.5 M H₂SO₄). The phytochemical compositions of the extracts were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC-MS). FTIR spectra revealed the presence of key functional groups, hydroxyl (O–H), amine (N–H), carbonyl (C=O), alkene (C=C), and aromatic rings, indicative of alcohols, phenols, amines, esters, ethers, and heterocyclic compounds. These functionalities are known to contribute to corrosion inhibition via adsorption onto metal surfaces, forming a protective film through lone pair electrons and π-bond interactions. GC-MS analysis identified major bioactive constituents including permethrin, caryophyllene, siloxane derivatives, ethylacridine, and naphthalenol, as well as fatty acids, terpenes, and nitrogenous compounds. These molecules possess multiple adsorption centers (O, N, S heteroatoms and π-electrons), enhancing their ability to coordinate with metal atoms and inhibit corrosion. The observed inhibition mechanism involves physical and chemical adsorption, which reduces metal ion dissolution and hydrogen evolution reactions. The data support the high corrosion inhibition potential of these plant extracts, positioning them as sustainable, environmentally benign alternatives to conventional synthetic inhibitors for acid corrosion control in industrial applications.
Keywords: Corrosion; Metals; Organic Compounds; Inhibitors; Extracts